Middleware services for atlases as part of spatial data infrastructures :Powerpoint - Köbben, B.J. (University of Twente, 2020)
This lecture presents: Limited and fragmented academic projects to keep atlas alive; Atlas as part of a Spatial Data Infrastructure; Mapping in a webservices environment; Architecture: middleware.